Plasmodium vivax Gametocytes Adherence to Bone Marrow Endothelial Cells - Salazar Alvarez, Luis Carlos; Vera Lizcano, Omaira; da Silva Barros, Dayanne Kamylla Alves; Baia-da-Silva, Djane Clarys; Monteiro, Wuelton Marcelo; Pimenta, Paulo Filemon Paolluci; de Lacerda, Marcus Vinicius Guimarães; Costa, Fabio Trindade Maranhão; Lopes, Stefanie Costa Pinto (Frontiers in Cellular and Infection Microbiology, 2021)
In a Plasmodium vivax infection, it was shown a proportionally increased on gametocyte distribution within the bone marrow aspirant, suggesting a role of this organ as a reservoir for this parasite stage. Here, we evaluated the ex vivo cytoadhesive capacity of P. vivax gametocytes to bone marrow endothelial cells (HBMEC) and investigated the involvement of some receptors in the cytoadhesion process by using transfected CHO cells (CHO-ICAM1, CHO-CD36 and CHO-VCAM), wild type (CHO-K1) or deficient in heparan and chondroitin sulfate (CHO-745). Ex-vivo cytoadhesion assays were performed using a total of 44 P. vivax isolates enriched in gametocyte stages by Percoll gradient in the different cell lines. The majority of isolates (88.9%) were able to adhere to HBMEC monolayer. ICAM1 seemed to be the sole receptor significantly involved. CD-36 was the receptor with higher adhesion rate, despite no significance was noticed when compared to CHO-745. We demonstrated that gametocyte P. vivax adheres ex vivo to bone marrow endothelial cells. Moreover, P. vivax gametocytes display the ability to adhere to all CHO cells investigated, especially to CHO-ICAM1. These findings bring insights to the comprehension of the role of the bone marrow as a P. vivax reservoir and the potential impact on parasite transmission to the vector.